Suppressor cell induction in vitro. VI. Production of suppressor factors to synthetic polypeptides GAT and (T,G)-A--L from cells of responder and nonresponder mice. - Kontianen, S; Howie, S; Maurer, P; Feldmann, M (1979)
The capacity of responder and nonresponder strains of mice to generate suppressor cells and factors to two antigens under MHC linked Ir gene control was investigated. Eight different H-2 types (H-2b,d,f,k,p,q,r,s) as well as seven independently derived strains (B10, BALB/c, CBA/Ca, A/St, DBA/2, P/J, SJL) were tested, and all yielded suppressor factor (SF) to (T,G)-A--L and GAT. This indicated that the genetic control of SF production was different from that of helper cell induction. Unlike previous reports of GAT suppressor extracts that GAT-specific supressor factors acted equally on both responder and nonresponder strains. As reported earlier with in vitro induced protein- (KLH) specific suppressor factors, GAT and (T,G)-A--L specific suppressor factors failed to show any genetic restriction in their function. The implications of these results for the general mechanism of Ir gene control are discussed.